A study of lameness in broilers chickens bred and reared in Brazilian commercial conditions - Almeida, Marco Aurélio Pereira de (2025)
Chicken meat consumption has remained high worldwide with fast-growing broilers being the most significant source of this protein. Both consumers and the organized poultry industry have shown increasing concern about balancing production intensity with the welfare of these animals. Locomotion problems in broilers are considered relevant in the context of animal welfare and impacts on production efficiency. Despite numerous studies on lameness in broilers, the potential consequences of locomotion issues, particularly pain and stress, from breeder hens and roosters to their offspring still requires further investigation. The main objective of this study was to evaluate possible impacts of lame and non-lame breeders on their direct broilers′ progeny. The assessments of the broilers and some environmental conditions were made upon the animal welfare protocol Welfare Quality®, complemented by mechanical pressure nociceptive threshold tests. The study was conducted in routine operational settings of the Brazilian poultry sector, including a breeder farm, an industrial-scale hatchery, and a broiler rearing farm. Parental generation breeders - both females and males - were individually categorized according to their gait score as lame (C) or non-lame (S). They were then paired into four mating groups: SS, SC, CS, and CC, where the first letter denotes the females condition and the second denotes the male′s. Fertile eggs were collected and incubated with identification of the parental treatment group. A total of 374 chicks were housed in the rearing farm in four separate replicates according to the parental treatment group and in mixed-sex groups without individual identification at placement. Breeders were primarily evaluated based on indicators such as egg production, embryonic viability, hatchability, and day-old-chick initial robustness. Broilers, the immediate progeny of these breeders, were evaluated at the end of the rearing cycle, focusing on locomotor indicators such as hock burn, footpad dermatitis, feather cleanliness, and gait score. These were recorded according to the parental treatment group and by sex of the grown up broilers in each experimental unit. Breeder performance indicators did not show significant differences that could associate performance variation with the contrasting treatments. In broilers, per the Welfare Quality® categories, the general condition of the animals and experimental facilities was assessed as enhanced. The average gait score was 1.43 on a scale from 0 to 5, where scores 4 and 5 indicate severe lameness. This mild lameness of the animals was consistent with the experimental conditions. Overall, no significant differences in lameness were observed among broilers from the respective parental treatments. However, some specific findings were peculiar: in the comparative analysis by sex, males showed higher gait score, thus worse locomotion problems, than females, yet exhibited higher nociceptive thresholds. That is, regardless of parental conditions, male broilers showed greater lameness but lower sensitivity to mechanical noxious stimulus pressure applied to their legs. This reduced sensitivity was even more pronounced in the left leg. Further within the sex-based analysis, male broilers descended from CS parental groups (lame females, non-lame males) had higher nociceptive thresholds than those from SS groups (both parents non-lame). These findings may stimulate a deeper investigation of the mechanisms responsible for such variations, in order to guide actions toward the desired resilience of the phenotypes in relation to lameness-related factors. There also appears to be an opportunity to explore mechanisms of nociceptive threshold, pain processing, brain lateralization, and chronic pain-induced analgesia in industrial poultry.